Motor Cognitive Coordination Training Program Based Android Apps (Journal of Physical Education Health and Sport, 2022)
Innovation in the field of education is still very rarely carried out by education practitioners, especially physical education and sports. Therefore, the researcher aims to create an innovation product in physical education learning by designing an android-based application that contains the MCCT (Motor Cognitive Coordination Training) program. Motor cognitive coordination training is an exercise method based on the kinetic life training method. Kinetic life training is a combined concept of movement coordination exercises and cognitive challenges, in which simple skills such as hand-eye coordination or continuous are combined with intellectual tasks to create complex exercises. The research method used in this study is the Research and Development (RD) method. The results showed that the effectiveness of using the MCCT application was 68% smaller than the MCCT program which was given by the direct instruction method, which was 78%. However, on some observation items, the effectiveness of the MCCT program based on the android application is greater than the MCCT program with the direct instruction method